Assessing People’s Values of Nature: Where Is the Link to Sustainability Transformations? - Stålhammar, Sanna (Frontiers in Ecology and Evolution, 2021)
The efforts to measure people’s current preferences and values of ecosystem services raises questions about the link to sustainability transformations. The importance of taking social and cultural values of nature into account is increasingly recognised within ecosystem services research and policy. This notion is informing the development and application of so-called social (or socio-cultural) valuation methods that seek to assess and capture non-material social and cultural aspects of benefits of ecosystems in non-monetary terms. Here, values refer to the products of descriptive scientific assessments of the links between human well-being and ecosystems. This precise use of values can be contrasted with normative modes of understanding values, as underlying beliefs and moral principles about what is good and right, and that influences science and institutions. While both perspectives on values are important for the biodiversity and ecosystem services agenda, values within this space have mainly been understood in relation to assessments and descriptive modes of values. Failing to acknowledge the distinction between descriptive and normative modes bypasses the potential mismatch between people’s current values and sustainability transformations. More refined methodologies to more ‘accurately’ describe social values risks simply giving us a more detailed account of what we already know—people in general do not value nature enough. We thus need additional justification for why or how peoples’ ‘mental states’ coincide with sustainability goals, and methods that go beyond focusing on current states to incorporate change and transformation.